化简1/(a+b)√(b/a+a/b+2)
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/09 18:18:21
化简1/(a+b)√(b/a+a/b+2)化简1/(a+b)√(b/a+a/b+2)化简1/(a+b)√(b/a+a/b+2)1/(a+b)√(b/a+a/b+2)=1/(a+b)√((a^2+b^2
化简1/(a+b)√(b/a+a/b+2)
化简1/(a+b)√(b/a+a/b+2)
化简1/(a+b)√(b/a+a/b+2)
1/(a+b)√(b/a+a/b+2)
=1/(a+b)√((a^2+b^2+2ab)/ab)
=1/(a+b)√(a+b)^2/ab
=1/(a+b) √((a+b)^2) √(1/ab)
=√ab
化简1/(a+b)√(b/a+a/b+2)
化简:|a+b|+|b-a|+|2b|
化简 (a+b)²+2a(a-1/2b)-3(a-b)(a+b)
化简(2a-b/a+b-b/a-b)除以a-2b/a+b
化简(2a-b/a+b-b/a-b)除以a-2b/a +b
化简:{[(2a-b)/(a+b)]-[b/(a-b)]}÷[(a-2b)/(a+b)]
化简:a-[b-2a-(a-b)]
化简(2a-b/a+b-b/a-b)÷a-2a/a-b
化简:[2/3a - 2/(a+b) * (a+b/3a - a - b)] / (a-b)/a
化简|a|+|-b|-|a-b|-|a+b|
化简 |b|-|a|+|a-b|+|a+b|
化简 |a-b|+|a+b|-|a-b|
-2a(a+b)+b(a+b)
化简(2a+b)^2-2(a-b)(2a-b)-1/2(2a-b)
化简-√(a+b)²+|b+a-1|.已知b
a^2+b(b+1)a+b^3 ,化简
化简a/b(a-b)-b/a(a-b)其中a=3 b=-2
a+b a-b----- -- ------a-b a+b -------------------------1------a^2 -b^2